Real-time tracking of curing process of an epoxy adhesive by X-ray photon correlation spectroscopy - Tsapatsaris, Leonidas; Wiegart, Lutz; Petrash, Stanislas; Baumeister, Tobias; Engels, Thomas; Endoh, Maya; Koga, Tadanori (Frontiers in Soft Matter, 2024)
In situ X-ray photon correlation spectroscopy (XPCS) was used to investigate the crosslinking kinetics of a two-component epoxy resin adhesive. The effect of external temperature on the crosslinking reaction was studied by subjecting the epoxy to different curing temperature profiles.The temporally resolved dynamics of fillers was tracked, which conveniently served as a probe of the internal dynamics of the thermoset network and allowed us to study the crosslinking process.The epoxy resins showed different relaxation processes depending on temperature, indicating a complex relationship between applied temperature and the development of stress/relaxation conditions related to the formation of the thermoset network and subsequent vitrification process.The epoxy was found to be highly temperature sensitive, with heating to elevated temperatures promoting gelation, but the vitrification process was not completed during the isothermal curing stage. Instead, cooling the sample to room temperature facilitated the final vitrification process.Finally, this paper contextualizes the results of this epoxy system within the broader field of XPCS on complex polymer systems and further advocates for XPCS as a fundamental technique for the study of complex polymers.